Profitabilitas dan Nilai Pasar : Seberapa Besar ROA dan ROE Mempengaruhi PBV Perusahaan Keuangan - Taufik Tahawa; Muhammad Fauzan; Rahmat Ghazali (Tangible Journal, 2026)
This study aims to examine the effect of Return on Equity (ROE) and Return on Assets (ROA) on Price to Book Value (PBV) in financial sector companies listed on the Indonesia Stock Exchange (IDX). The study employed a quantitative approach using an explanatory research design and secondary data obtained from the companies' annual financial statements for the 2025 period. The research sample was selected using a purposive sampling technique based on predetermined criteria. Data were analyzed using multiple linear regression analysis preceded by classical assumption tests, followed by t-tests and the coefficient of determination. The results indicate that ROE and ROA each have a positive and significant effect on PBV. Furthermore, the R Square value of 0.400 indicates that 40% of the variation in PBV can be explained by ROE and ROA, while the remaining 60% is influenced by other factors outside the research model. These findings suggest that higher profitability contributes to increasing firm value. Therefore, company management should optimize the utilization of assets and shareholders' equity to enhance investor confidence and improve the company's market value.